Influence of Membrane Fouling and Reverse Salt Flux on Membrane Impedance of Forward Osmosis Microbial Fuel Cell - Yang Zhao; Liang Duan; Xiang Liu; Yonghui Song (Membranes, 2022)
The forward osmosis membrane (FO membrane) is an emerging wastewater treatment technology in bioelectricity generation, organic substrate removal and wastewater reclamation. Compared with traditional membrane materials, the FO membrane has a more uniform water content distribution and internal solution concentration distribution. In the past, it was believed that one of the important factors restricting power generation was membrane fouling. This study innovatively constructed a mass transfer model of a fouling membrane. Through the analysis of the hydraulic resistance coefficient and the salt mass transfer resistance coefficient, the driving force and the tendency of reverse salt flux during membrane fouling were determined by the model. A surprising discovery was that the fouling membrane can also achieve efficient power generation. The results showed that the hydraulic resistance coefficient of the fouling membrane increased to 4.97 times the initial value, while the salt mass transfer resistance coefficient did not change significantly. Meanwhile, membrane fouling caused concentration polarization in the FO membrane, which enhanced the reverse trend of salt, and the enhancement effect was significantly higher than the impact of the water flux decline caused by membrane pollution. This will make an important contribution to research on FO membrane technology as sustainable membrane technology in wastewater treatment.